2016
DOI: 10.18632/oncotarget.13496
|View full text |Cite
|
Sign up to set email alerts
|

MBD3 inhibits formation of liver cancer stem cells

Abstract: Liver cancer cells can be reprogrammed into induced cancer stem cells (iCSCs) by exogenous expression of the reprogramming transcription factors Oct4, Sox2, Klf4 and c-Myc (OSKM). The nucleosome remodeling and deacetylase (NuRD) complex is essential for reprogramming somatic cells. In this study, we investigated the function of NuRD in the induction of liver CSCs. We showed that suppression of methyl-CpG binding domain protein 3 (MBD3), a core subunit of the NuRD repressor complex, together with OSKM transduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Overall, our findings indicate a tumor suppressor function of MBD3, a subunit of the NuRD complex, in human myeloid leukemia. Gut‐specific conditional inactivation of Mbd3 causes increased susceptibility to tumorigenesis, highlighting its tumor suppressor role (52, 53). Loss of MBD3 has been also linked with pancreatic cancer cell invasion and metastasis (54).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our findings indicate a tumor suppressor function of MBD3, a subunit of the NuRD complex, in human myeloid leukemia. Gut‐specific conditional inactivation of Mbd3 causes increased susceptibility to tumorigenesis, highlighting its tumor suppressor role (52, 53). Loss of MBD3 has been also linked with pancreatic cancer cell invasion and metastasis (54).…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of CD44 helps to understand the molecular mechanism underlying liver iCSCs. Former studies of our lab find that CD44 is overexpressed in the nucleus of C3A-iCSCs, shMBD3-iCSCs and C3A-c-Jun-iCSCs 20, 21. This phenomenon caused our great concern.…”
Section: Introductionmentioning
confidence: 99%
“…C3A-iCSCs were generated by OSKM transduction and possessed a faster proliferation rate, with PES1 up-regulation promoting proliferation Reprogramming of C3A cells was performed in preliminary work with four reprogramming factors, Oct4, Sox2, Klf4 and c-Myc (OSKM). These cells were named C3A-iCSCs and are preserved in our laboratory [25,26]. We found that the growth of C3A-iCSCs was faster compared with C3A.…”
Section: Resultsmentioning
confidence: 98%
“…Reprogramming of C3A cells was performed in preliminary work with four reprogramming factors, Oct4, Sox2, Klf4 and c‐Myc (OSKM). These cells were named C3A‐iCSCs and are preserved in our laboratory . We found that the growth of C3A‐iCSCs was faster compared with C3A.…”
Section: Resultsmentioning
confidence: 98%